A High‐Performance Room‐Temperature Li||Ga–Sn Liquid Metal Battery for Grid Energy Storage. Issue 9 (8th September 2021) - Wang, Kaizhao; Hu, Jin; Chen, Tianyou; Tang, Jingtao; Wang, Zhiyi; Fan, Ningning; Zhang, Weijun; Wang, Kaijun
Abstract : A room‐temperature liquid metal battery with a solid lithium anode electrode and gallium–tin (Ga–Sn) alloy cathode electrode is reported. The Li‖Ga–Sn battery has fast reaction kinetics, a satisfactory specific capacity, high energy efficiency, good rate performance, and stable cyclic reversibility, which is a promising choice for power grid energy storage applications. More details can be found in article number 2100330, Jin Hu, Kaijun Wang, and co‐workers.